Production, engine performance, combustion, emission characteristics and economic feasibility of biodiesel from waste cooking oil: A review. Issue 1 (22nd September 2019) - Rekhate, Chhaya; Prajapati, Abhinesh Kumar
Abstract: The depletion of fossil fuel reserves and increasing demands for diesel are considered to be important triggers for many of the initiatives that have been taken to search for possible sources for the production of biodiesel from materials available within the country. It is possible to produce biodiesel from waste/used cooking oils (WCO) that is comparable in quality to that of fresh vegetable oil. Not only does reuse of WCO, which can otherwise harm human health, reduce the burden on the government of treating oily wastewater, disposing of the waste, and maintaining public sewers, it also significantly lowers the production cost of biodiesel. In the process of frying, oil undergoes many reactions, leading to the formation of a number of undesirable compounds, such as polymers, free fatty acids, and many other chemicals. This poses challenges in the transesterification of WCO. This article covers different techniques in the production of biodiesel from WCO. It also compares combustion, emissions, and engine performance characteristics of biodiesel from WCO as well as factors affecting biodiesel production from WCO and its economic feasibility.